2022
DOI: 10.1186/s12964-022-00852-0
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activity‐modifying protein 1 regulates mouse skin fibroblast proliferation via the Gαi3-PKA-CREB-YAP axis

Abstract: Background Skin innervation is crucial for normal wound healing. However, the relationship between nerve receptors and wound healing and the intrinsic mechanism remains to be further identified. In this study, we investigated the role of a calcitonin gene-related peptide (CGRP) receptor component, receptor activity‐modifying protein 1 (RAMP1), in mouse skin fibroblast (MSF) proliferation. Methods In vivo, Western blotting and immunohistochemical (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…They found that RAMP1 expression levels were altered during skin wound healing. Moreover, RAMP1 overexpression (OE) promoted cell proliferation and was associated with increased yes-associated protein expression and altered expression patterns of G proteins ( Yin et al, 2022 ). Interestingly, CALCRL-RAMP1 has been shown to have mechanoresponsive properties and is involved in mechanical force transduction in macrophages in mice, thereby pointing to a role for RAMP1 in innate immunity ( Muschter et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that RAMP1 expression levels were altered during skin wound healing. Moreover, RAMP1 overexpression (OE) promoted cell proliferation and was associated with increased yes-associated protein expression and altered expression patterns of G proteins ( Yin et al, 2022 ). Interestingly, CALCRL-RAMP1 has been shown to have mechanoresponsive properties and is involved in mechanical force transduction in macrophages in mice, thereby pointing to a role for RAMP1 in innate immunity ( Muschter et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 43 Its overexpression stimulates the proliferation of MSF through the Gαi3–PKA–CREB–YAP axis. 11 Furthermore, RAMP1 deficiency severely impairs organ mass recovery and hepatocyte proliferation after acute and chronic liver injury. 14 The protective effect of RAMP1 in different organs is supported by abundant evidence.…”
Section: Discussionmentioning
confidence: 99%
“… 8 RAMP1 has been studied extensively due to its ability to reduce inflammation, 9 , 10 and promote injury repair. 11 , 12 As the alteration of its expression can modulate the sensitivity of CGRP, and as it binds to and regulates CLR expression, the targeting of RAMP1 may be a promising approach to the alteration of CGRP activity. 13 RAMP1-deficient mice exhibit impaired organ mass recovery and hepatocyte proliferation, which stimulates the expression and activity of yes-associated protein (YAP)/TAZ after 70% hepatectomy or repeated intraperitoneal injection of carbon tetrachloride.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptides such as vasoactive intestinal peptide (VIP), calcitonin gene‐related peptide (CGRP), and SP also contribute to wound healing and reepithelialization 213–215 . Mouse skin fibroblasts express RAMP1, the receptor for CGRP, activation of which increases their proliferation through a YAP signaling mechanism 216 and SP stimulates keratinocyte migration and increases the rate of reepithelialization during wound healing in mice 200 . SP is also involved in the recruitment of mesenchymal stromal cells to damaged tissues, and stimulation of progenitor cell proliferation by activating the neurokinin‐1 receptor 217,218 .…”
Section: Nerves and Wound Repairmentioning
confidence: 99%